2015
DOI: 10.1038/eye.2015.51
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of uveal melanoma based on race in 8100 patients: The 2015 Doyne Lecture

Abstract: A retrospective, nonrandomized, interventional case series of 8100 patients with uveal melanoma were evaluated for melanoma-related metastasis based on patient race. The patient race was Caucasian (n = 7918, 98%), Hispanic (n = 105, 1%), Asian (n = 44, o1%), or African American (n = 33, o1%). On the basis of race (Caucasian, Hispanic, Asian, and African American), significant differences were noted in mean age at presentation (58, 48, 44, and 52 years; Po0.001), distance of posterior tumor margin to foveola (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
108
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(132 citation statements)
references
References 14 publications
(25 reference statements)
8
108
2
2
Order By: Relevance
“…Of the cases registered, 97.8% occurred in the white population [5]. There is a strong difference in the incidence for different ethnic groups: the annual age-adjusted incidence is 0.31 for Afro-Americans, 0.38 for Asians, 1.67 for Hispanics, and 6.02 for non-Hispanic whites [6], yet prognosis does not differ for ethnic groups [7]. The European Cancer Registry-based study on survival and care of cancer patients (EUROCARE) for the years 1983–1994 reported similar incidence rates with a characteristic increase from south to north, from <2 per million in Spain and Southern Italy to >8 per million in Norway and Denmark [8].…”
Section: Clinical Features Of Uveal Melanomamentioning
confidence: 99%
“…Of the cases registered, 97.8% occurred in the white population [5]. There is a strong difference in the incidence for different ethnic groups: the annual age-adjusted incidence is 0.31 for Afro-Americans, 0.38 for Asians, 1.67 for Hispanics, and 6.02 for non-Hispanic whites [6], yet prognosis does not differ for ethnic groups [7]. The European Cancer Registry-based study on survival and care of cancer patients (EUROCARE) for the years 1983–1994 reported similar incidence rates with a characteristic increase from south to north, from <2 per million in Spain and Southern Italy to >8 per million in Norway and Denmark [8].…”
Section: Clinical Features Of Uveal Melanomamentioning
confidence: 99%
“…No conclusive results have been published on the association between iris colour, skin colour and the development of CoM. Pigmentation of the tumours themselves was investigated as well: amelanotic cutaneous melanoma has a significantly worse survival compared with melanotic cutaneous melanoma,13 and one analysis found that low tumour pigmentation was similarly associated with a worse clinical outcome in UM 14. Low tumour pigmentation has been associated with a worse prognosis in CoM,15 but this was investigated in a limited number of patients as the disease is so rare.…”
Section: Introductionmentioning
confidence: 99%
“…In the Collaborative Ocular Melanoma Study (COMS), as well as a more recently published series of 8,100 patients with UM, 97%-98% of patients were Caucasian, with Asian patients representing < 1% of patients in both cohorts. (8,9) Aside from significant epidemiological heterogeneity, there is also marked biological diversity in UM. In recent years, the genetic abnormalities in UMs have been found to be distinct from those in cutaneous melanomas.…”
mentioning
confidence: 99%